The effectiveness of Augmented Reality based Learning on Vocational Competencies of Vocational School Students - Herlandy, Pratama Benny; Azim, Fauzan; Majid, Nuur Wachid Abdul (Universitas Hamzanwadi, 2020)
This research is based on limited laboratories in vocational high schools in the city of Pekanbaru. Students are could not to use one computer device (PC) for each. The actual condition is one PC is used by 2-3 students. This fact has an impact on the achievement of vocational competence. The proposed solution is to present a virtual laboratory concept based on Augmented Reality (AR). The purpose of this study was to measure the effectiveness of AR based learning media on the achievement of vocational competencies of. The type of research applied is equals-experimental with two groups pretest-posttest design method. The population and sample in this study were the Multimedia Study Program of SMK Muhammadiyah 2 Pekanbaru City. The results obtained were learning to use AR media is effective for increasing the learning outcome in the basic computer network material. The use of augmented reality-based learning media can be applied to vocational learning in SMK with material adjustments designed according to the needs of the applicable curriculum.